2011
DOI: 10.1039/c1cc15843k
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(iii)-catalyzed oxidative carbonylation of benzamides with carbon monoxide

Abstract: An efficient strategy for the oxidative carbonylation of aromatic amides via C-H/N-H activation to form phthalimides under Rh(III) catalyst has been developed. The reaction shows a preference for C–H bonds of electron-rich aromatic amides and tolerates a variety of functional groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(56 citation statements)
references
References 30 publications
0
53
0
3
Order By: Relevance
“…In 2011, Rovis and co-workers developed a rhodium(III)-catalyzed oxidative carbonylation of benzamides to form phthalimides with Ag 2 CO 3 as the oxidant (Scheme 34a). C-H bonds of electron-rich aromatic amides showed better activity [102]. Chatani and co-workers found that utilizing a bidentate system, aromatic amides having a pyridin-2-ylmethylamine moiety could undergo cyclocarbonylation through C-H bond activation in the presence of catalytic amount of Ru 3 (CO) 12 and CO (Scheme 34b).…”
Section: Synthesis Of Five-membered Heterocycles Via Oxidative Carbonmentioning
confidence: 97%
“…In 2011, Rovis and co-workers developed a rhodium(III)-catalyzed oxidative carbonylation of benzamides to form phthalimides with Ag 2 CO 3 as the oxidant (Scheme 34a). C-H bonds of electron-rich aromatic amides showed better activity [102]. Chatani and co-workers found that utilizing a bidentate system, aromatic amides having a pyridin-2-ylmethylamine moiety could undergo cyclocarbonylation through C-H bond activation in the presence of catalytic amount of Ru 3 (CO) 12 and CO (Scheme 34b).…”
Section: Synthesis Of Five-membered Heterocycles Via Oxidative Carbonmentioning
confidence: 97%
“…[51a] Mit dem [{RhCp*Cl 2 } 2 ]/AgSbF 6 -Katalysatorsystem, das sich bisher als effektiver Katalysator in Reaktionen von Alkenen, Alkinen, [53] Allenen [54] sowie CO, [55] Chloraminen [56] und verschiedenen Elektrophilen [57] erwiesen hat, gelang die Arylierung von Benzamiden und einigen Acetophenonen mit Arylhalogeniden, wobei die Halogeneinheit generell intakt blieb. Bemerkenswerterweise blieb die ortho-Position zum Halogenid immer unberührt, sodass bei Verwendung 1,3-disubstituierter Brombenzole selektiv wertvolle meta-Bromsubstituierte Biarylsysteme aufgebaut werden kçnnen, welche die Mçglichkeit zur weiteren Modifikation bieten (Schema 14).…”
Section: Angewandte Aufsätzeunclassified
“…Rh(III)-complex-catalyzed formation of phthalimides by oxidative carbonylation of aromatic amides via C-H/N-H activation was developed by Rovis and co-workers in 2001 [146]. This was based on previous reports of coupling of benzamide and α,β-unsaturated amides with alkynes to produce isoquinolones and pyridones utilizing Rh(III)-catalyzed C-H activation [147][148][149][150][151][152][153][154][155].…”
Section: %mentioning
confidence: 98%